The current status, challenges and prospects of native pig production and large-scale farming in Laos - Xayalath, Somsy; Josef, Ratky; Sol Valmoria Ortega, Arth David; Osotsi, Joab Malanda; Novotni-Danko, Gabriella (Acta Agraria Debreceniensis, 2025)
This review aimed to investigate the potential native pig development and the trend that large-scale farming may influence native pig production in Laos. The review found that native pigs were estimated to be around 88% of the total pig population in Laos in 2023. Commercial pig farming was found only in the main cities, particularly the central and southern provinces, which increased from 578 in 2019 to 703 farms in 2022 and 737 farms in 2023. Due to the serious economic crisis starting in 2021, many Lao pig producers stopped their businesses, leading to the decline of the commercial pig population by almost 30% in 2023 compared to 2022. The average pork per capita consumption in Laos in 2021 was estimated at about 14.2 kg. Though not as high as the backyard, commercial farms still contribute essentially to the pork supply in Laos (12%), increasing the volume from 87,628 tonnes in 2015 to 137,775 tonnes in 2024. The main native pig producers are small-scale rural farmers who have not yet improved productivity or reproductive performance, and the main purpose of their production is household consumption rather than market orientation. However, farmers, mainly in the main cities, improved them by cross-breeding native pig sows with Duroc boar for better lean meat. The main challenges for native production in Laos include poor farm setup and management, high cost of commercial feed, and poor breeding and genetic management. Therefore, creating awareness of the benefits of setting up a pig farm and management, providing better option strategies for utilising locally available feeds, and providing better strategies on pig breeding could improve native pig production in Laos.